(untitled) (REMUNOM, 2024)
Aging is associated with several physical and physiological changes, including loss of muscle mass and consequently function, which is called sarcopenia. In the elderly, it is multifactorial and can be exacerbated by diseases and nutritional, hormonal, endocrine, neurological, obesity, immunological, cardiovascular, and pulmonary factors, as well as an inadequate lifestyle. Sarcopenia manifests itself with the emergence of several dysfunctions such as: gait instability, weakness and slowness when walking, frequent falls, loss of weight or muscle mass, difficulty climbing stairs, carrying heavy objects, and getting up from a chair alone. Among the existing treatments, strength training in the elderly is a type of exercise that has been shown to be effective in delaying the decline in strength and muscle mass; patients experience improved gait and balance, and a reduced risk of falls. Thus, the objective of this study was to describe the relationship between resistance training for hypertrophy in elderly individuals and their improvement in quality of life. Therefore, the results found suggest that resistance training performed at high speed is an efficient strategy and should be adopted in a training program for elderly individuals in order to increase their functional capacity. Keywords: Sarcopenia; Elderly; Strength Training